Pemberian Penyuluhan, Tehnik Relaksasi Napas Dalam, Hipnosis 5 Jari, Dan Senam Untuk Lansia Dengan Hipertensi Yang Mengalami Kecemasan - Angelina Eka; Yosef A. Beo; Paskaliana H Danal; Yuliana Reginadis R. Crowa; Lusia H. Mariati; Waldetrudi Wahyuni; Maria Y. Asung; Melania A Meo; Reinaldis Mala (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
Every year, hypertension become the main cause of the death in the world and known as the silent killer. Untreated hypertension can cause various problems in the body especially the brain, heart and kidneys. Age, heredity, and lifestyle are factors that cause hypertension. The elderly is a group susceptible to hypertension due to physiological changes in blood vessels because of age related. Elderly people with hypertension often experience anxiety which can increase blood pressure. The purpose of this community service is to increase knowledge and lifestyle in doing sports and reduce anxiety in the elderly with hypertension in the Kuwus district of West Manggarai. The respondents of this study were 25 hipertensive elderly clients. The activity was carried out in 3 stages, namely 1) measuring blood pressure and anxiety levels 2) counseling about hypertension and anxiety 3) Education on deep breathing relaxation and 5 finger hypnosis techniques, and 4) Joint exercise. Based on the paired t-test result, it was identified the difference of knowledge (pvalue: 0.001) and attitude (pvalue: 0,005) between pre and post intervention. The results of the implementation show that after the knowledge activity has increased and the anxiety of the elderly has decreased. Relaxation and exercise techniques can be applied to the elderly in the future